KPOP Ilonggo fans consumption of Kpop MTV content - Bertuldes, Relly; Montalvo, Johna Raf.; Silvederio, Julie Ann Mae. (2014.)
The popularity of Korean popular (Kpop) music among the Ilonggo fans aged 15-24 years is the main focus of this research, a local extension to what was nationally probed by Sarah Kristine M. Alanzon in 2011. An online survey among 196 Ilonggo Kpop fans of the Korean groups Girl?s Generation, Super Junior, Shinee, Bigbang and EXO. The researchers determined the variables of ?consumption of Kpop content, cultural offerings present in Kpop content, and the needs of the fans satisfied by Kpop content? (Alanzon, 2011). It was found out that the Ilonggo respondents are highly exposed to Korean popular music, consumed these media texts through various media channels, predominantly the Internet. Among the various cultural offerings, the research found out that the visual aspect has the most impact among Ilonggo fans and choreography is its most appealing facet. Aside form surveillance, identification and interaction; entertainment was discovered to be the most gratified need of Ilonggo Kpop fans. Despite the apparent language differences, it was ascertained that it is not a barrier to fans? consumption but rather paves way to language acquisition. Particular factors were hereby uncovered: increasing accessibility of the Internet; entertainment, choreography in particular; language acquisition and; new knowledge acquirement. These factors found in media of international source, such as the phenomenal Kpop Music TV (MTV), can be a tool to help the local media enhance MTV productions, leading to increased consumption among the Ilonggo MTV viewers.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: KPOP fans -- Ilonggo; KPOP content -- Consumption; KPOP music; KPOP MTV